Formulation and Antioxidant Evaluation of Anti-Aging Moisturizer Containing Peperomia pellucida Extract Loaded Nanostructured Lipid Carrier - Maulita, Silvia; Devianti, Siti; Laila, Nur; Hailiyah, Dini Siva; Sukmawati, Dian Ayu; Danimayostu, Adeltrudis Adelsa; Adianingsih, Oktavia Rahayu (Jurnal Kefarmasian Indonesia, 2025)
Peperomia pellucida, commonly known as Chinese betel, contains antioxidants and anti-inflammatory compounds, which are potential candidates for active ingredients in anti-aging topical moisturizer formulations. However, its low lipid solubility requires a modified delivery system, such as nanostructured lipid carriers (NLC). This study aimed to determine the optimum lipid concentration and lipid phase ratio for NLC formulation, evaluate the anti-aging potential of Peperomia pellucida extract-loaded NLC, and assess the characteristics of the NLC-based moisturizer. NLC was prepared using the high shear homogenization method and then characterized for its physical properties. Antioxidant activity was evaluated using the DPPH method, while the stability of the moisturizer was assessed through a six-cycle storage cycling test. NLC F1, containing 5% total lipid with a solid-to-liquid lipid ratio of 3:2, had the smallest particle size among all formulations and was selected as the optimal formula. The antioxidant test of NLC F1 revealed a spheroidal morphology, confirmed by TEM, and an IC50 value of 113.45 ppm, indicating moderate antioxidant activity. When incorporated into a moisturizer, the formulation maintained stable organoleptic properties, homogeneity, pH, spreadability, and adhesiveness over six test cycles, despite a decrease in viscosity. The optimized lipid composition produced a stable NLC-based moisturizer loaded with Peperomia pellucida extract, showing moderate antioxidant activity and favorable physicochemical characteristics, supporting its potential as an anti-aging cosmeceutical product.